2016
DOI: 10.21909/sp.2016.01.703
|View full text |Cite
|
Sign up to set email alerts
|

Different Modalities of Using Facebook: The Influence of Actual Social Relations, Wellbeing, and Attitude Towards the Medium

Abstract: Abstract:The online social networks attract the social scientists' attention because of their large diffusion and their social and psychological impact. The majority of the studies focus on Facebook because it is the largest one. There are contrasting opinions on the positivity of that social medium. It is not possible to reach univocal results considering the use of Facebook as a whole. It is better to distinguish different modalities of use. This study investigates these modalities and predicts them on a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…Gender is considered a key variable in understanding SNS use (Brooks & Longstreet, 2015;Dhir, Pallesen, Torsheim, & Andreassen, 2016;Haferkamp, Eimler, Papadakis, & Kruck, 2012;McAndrew & Jeong, 2012;Pfeil, Arjan, & Zaphiris, 2009;Tartaglia, 2016). According to Haferkamp and colleagues (2012), men primarily consider SNS as a pragmatic communication medium but not a relevant platform for self-portrayal, whereas women seem to be driven by a more hedonistic motive of self-presentation, which makes them more concerned about how they are perceived by others.…”
Section: The Use Of Sns From a Gender Perspectivementioning
confidence: 99%
“…Gender is considered a key variable in understanding SNS use (Brooks & Longstreet, 2015;Dhir, Pallesen, Torsheim, & Andreassen, 2016;Haferkamp, Eimler, Papadakis, & Kruck, 2012;McAndrew & Jeong, 2012;Pfeil, Arjan, & Zaphiris, 2009;Tartaglia, 2016). According to Haferkamp and colleagues (2012), men primarily consider SNS as a pragmatic communication medium but not a relevant platform for self-portrayal, whereas women seem to be driven by a more hedonistic motive of self-presentation, which makes them more concerned about how they are perceived by others.…”
Section: The Use Of Sns From a Gender Perspectivementioning
confidence: 99%
“…Instead, other studies found no relation between self-esteem and Facebook use ( Skues, Williams, & Wise, 2012 ). As some scholars have suggested, the literature may be inconsistent because studies have considered Facebook as a whole without distinguishing between different modalities of use or motivations to utilize the social network ( Rae & Lonborg, 2015 ; Tartaglia, 2016 ). Generally, people who communicate easily with others face to face have less need to spend a great deal of time online, but when considering the specific ways Facebook can be used, a different result can be found ( Wilson, Fornasier, & White, 2010 ).…”
Section: Facebook and Self-esteemmentioning
confidence: 99%
“…Generally, people who communicate easily with others face to face have less need to spend a great deal of time online, but when considering the specific ways Facebook can be used, a different result can be found ( Wilson, Fornasier, & White, 2010 ). A recent study ( Tartaglia, 2016 ) has shown three different modalities of using Facebook, i.e., social interaction, simulation, and search for relations. The first is the use of the social network for interaction with friends and for self-expression.…”
Section: Facebook and Self-esteemmentioning
confidence: 99%
See 2 more Smart Citations